Research progress of hereditary diffuse leukoencephalopathy with spheroids - Fei-xia ZHAN; Li CAO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Hereditary diffuse leukoencephalopathy with spheroids (HDLS) is a rare and progressive disorder of hereditary white matter degeneration in the central nervous system (CNS). Clinically, the prominent manifestations are progressive cognitive impairment, personality change, mental and behavioral symptoms and movement disorders. Imaging is mainly characterized by asymmetric, patchy or diffuse white matter lesions. Distinctive neuropathology revealed diffuse white matter lesions with marked axonal degenerative spheroids. Colony stimulating factor 1 receptor (CSF1R) gene is currently the only pathogenic gene identified. This article reviews the research progress in clinical study, genetics and pathogenesis of the disease.